Germany in multipolar world and Serbia's strategic options - Ćurčić Petar S. (Војно дело, 2022)
The paper analyzes the position of the Federal Republic of Germany in international relations today and based on that policy, possible guidelines for the Republic of Serbia in its strategic actions in the upcoming period are given. The first goal of the research was to consider the relationship of official Berlin to the European Union, the United States, Russia, China and the rest of the world. Berlin's tendency to further strengthen the institutions, monetary, foreign and defense policy of the European Union has been present for decades. However, since 2008, that policy has been going through constant challenges. The Greek debt crisis, Brexit, the migrant crisis, the recession, a new wave of debts by European countries due to the Covid-19 pandemic and the war in Ukraine have put the authorities in Berlin in a difficult position. The failure of Germany and France to establish a unified EU security policy, the impossibility of peace initiatives around Ukraine and the consistent monitoring of Washington's policy have limited the EU ability to project power in other parts of the world. In addition to Russia, it is also obvious that the growing antagonism towards the People's Republic of China has been noticed recently, which threatens to affect very good economic relations The second goal of the paper is to offer Serbia's strategic options based on global trends, and in the context of German policy towards the Western Balkans. The Serbian focus on the European integration and the proclaimed policy of neutrality with a strong commitment to the European peace can be an incentive for joint affairs of the two countries. Particularly problematic is Berlin's attitude towards the self-proclaimed independence of the interim institutions in Prishtina. The opposing positions of Germany and Serbia, however, can be attributed to various regional initiatives such as the Berlin Process and particularly the Open Balkans. The attempts to further escalate the conflict or confrontation of Serbia towards the environment would adversely affect the position of Serbs in the surrounding countries and would also weaken economic exchange, which is traditionally oriented towards the European countries. However, official Belgrade should also work on strengthening internal capacities, primarily defensive, economic, administrative and demographic, so that it can have a high level of readiness in case of possible challenges.